Mampukah Program CSR Mengatasi Konflik Pencemaran Lingkungan antara Perusahaan dengan Masyarakat Lokal - Neny Adriani; Tjiptohadi Sawarjuwono (Jurnal Akuntansi dan Bisnis, 2013)
Several studies in many developing countries presents examples of conflicts events between mining companies with the surrounding community. Mining companies usually much blamed for carelessness on the environment, human rights abuses, discriminatif management, policy and operations that are less favor. Conclusion of these studies show that, if the company more "responsible" with CSR programs that suit the needs of society and the state in the areas of operations, community resistance to its operations could be minimize. Accordingly, this study tries to question, does CSR plays a role in the resolution of conflict between one of the major mining companies in Indonesia, Pertamina, with local communities. The study was conducted with a narrative approach. The data obtained through interviews and documentation from internal Pertamina’s weekly magazine. The analysis has done by linking the theory with the data that has been collected to answer the research questions. The results showed that, under certain conditions, CSR does play a role in conflict resolution.